Effect of Preoperative Intravenous and Inhalational Dexmedetomidine on the Hemodynamic Response of Laryngoscopy: A Prospective Double-blinded Randomized Study - Shivanya Singh; Priyanka Gupta; Mridul Dhar; Arhan Pasha (Wolters Kluwer Medknow Publications, 2024)
Objective: Laryngoscopy induces potent noxious stimuli causing reflex autonomic activation manifested by an increase in blood pressure and heart rate (HR). Various drugs with different routes have been tried to prevent this response. The literature comparing inhalational dexmedetomidine with intravenous (IV) dexmedetomidine to prevent laryngoscopy response is limited. Methods: A total of 150 American Society of Anesthesiologists Physical Status Class I/II, undergoing elective surgery requiring laryngoscopy and intubation, were included and randomized into two groups. Patients in Group DINH received nebulized dexmedetomidine (1 μg/kg) and in Group DIV received IV dexmedetomidine (0.5 μg/kg), 15 min before anesthesia induction. For blinding, nebulized or IV saline was used simultaneously. The primary outcome was to compare the mean arterial pressure (MAP) and HR at laryngoscopy, intubation, and 1, 5, and 10 min after intubation. The secondary outcome was to compare sedation, following the administration of dexmedetomidine, propofol consumption during induction, and any side effects. Findings: There was no significant difference in MAP (mmHg) postlaryngoscopy and intubation (immediate after intubation 78.5 ± 11.3 vs. 82.3 ± 16.0, P = 0.093). The mean HR was clinically similar in both groups postlaryngoscopy and intubation (immediate after intubation, 80.9 ± 12.5 vs. 76.3 ± 10.9). Patients in the DIV group were more sedated than the DINH (Ramsay Sedation Scale 3-4 vs. 1-2, P < 0.001). Bradycardia was seen in eight patients of the DIV group only. Conclusion: Preoperative nebulized dexmedetomidine is as effective as and safer than IV dexmedetomidine in preventing laryngoscopic response among adults.